Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 43699 by Meritguide1234 last updated on 14/Sep/18

Commented by Meritguide1234 last updated on 14/Sep/18

complete it

completeit

Commented by maxmathsup by imad last updated on 14/Sep/18

let I = ∫  (((1−(√(1+x+x^2 )))^2 )/(x^2 (√(1+x+x^2 ))))dx  we have  I= ∫ ((1−2(√(1+x+x^2 ))+1+x+x^2 )/(x^2 (√(1+x+x^2 ))))dx  = ∫   (dx/(x^2 (√(1+x+x^2 ))))dx −2 ∫  (dx/x^2 )   + ∫   ((√(1+x+x^2 ))/x^2 )dx  but  −2 ∫ (dx/x^2 ) =(2/x) +c   and  ∫     (dx/(x^2 (√(1+x+x^2 )))) = ∫   (dx/(x^2 (√((x+(1/2))^2  +(3/4)))))  =_(x+(1/2)=((√3)/2)sh(t))     ∫     (1/((((√3)/2)sh(t)−(1/2))^2 ((√3)/2)ch(t))) ((√3)/2) ch(t)dt  = ∫     ((4dt)/(((√3)sh(t)−1)^2 )) = ∫     ((4dt)/(3sh^2 (t)−2(√3)sh(t) +1))  = ∫     ((4dt)/(3((1+ch(2t))/2)−2(√3)sh(t)+1)) =8 ∫    (dt/(3 +3ch(2t)−4(√3)sh(t) +2))  =8 ∫    (dt/(3 +3 ((e^(2t)  +e^(−2t) )/2) −4(√3)((e^t  −e^(−t) )/2)+2)) =16 ∫     (dt/(6 +3 e^(2t)  +3e^(−2t)  −4(√3)e^t +4(√3)e^(−t) +4))  =_(e^t  =u)     16  ∫       (du/(u{ 10 +3u^2  +3u^(−2)  −4(√3)u +4(√3)u^(−1) }))  =16 ∫  (du/(10u +3u^3  +3u^(−1)  −4(√3)u^2  +4(√3)))  =16 ∫   ((udu)/(10u^2  +3u^(4 )  +3 −4(√3)u^3  +4(√3)u ))  let decompose  F(u) = (u/(3u^4  −4(√3)u^3  +10u^2  +4(√3)u +3))  ...be continued...

letI=(11+x+x2)2x21+x+x2dxwehaveI=121+x+x2+1+x+x2x21+x+x2dx=dxx21+x+x2dx2dxx2+1+x+x2x2dxbut2dxx2=2x+canddxx21+x+x2=dxx2(x+12)2+34=x+12=32sh(t)1(32sh(t)12)232ch(t)32ch(t)dt=4dt(3sh(t)1)2=4dt3sh2(t)23sh(t)+1=4dt31+ch(2t)223sh(t)+1=8dt3+3ch(2t)43sh(t)+2=8dt3+3e2t+e2t243etet2+2=16dt6+3e2t+3e2t43et+43et+4=et=u16duu{10+3u2+3u243u+43u1}=16du10u+3u3+3u143u2+43=16udu10u2+3u4+343u3+43uletdecomposeF(u)=u3u443u3+10u2+43u+3...becontinued...

Commented by MJS last updated on 14/Sep/18

there′s a magic word and I seem to remember  it starts with “p”.

theresamagicwordandIseemtorememberitstartswithp.

Commented by Meritguide1234 last updated on 15/Sep/18

Answered by tanmay.chaudhury50@gmail.com last updated on 14/Sep/18

∫((1−2(√(1+x+x^2 ))  +1+x+x^2  )/(x^2 (√(1+x+x^2 )) ))dx  ∫(dx/(x^2 (√(1+x+x^2 )) ))−2∫(dx/x^2 )+∫(((√(1+x+x^2 )) )/x^2 )dx  I=I_1 −2I_2 +I_3   I_1 =∫(dx/(x^2 (√(1+x+x^2 )) ))  t=(1/x)dx  dt=−(dx/x^2 )  ∫((−dt)/(√(1+(1/t)+(1/t^2 ))))  ∫((−tdt)/(√(t^2 +t+1)))(/)  ((−1)/2)∫((2t+1−1)/(√(t^2 +t+1)))dt  =(1/2)∫(dt/(√(t^2 +t+1)))−(1/2)∫((d(t^2 +t+1))/(√(t^2 +t+1)))  =(1/2)∫(dt/(√(t^2 +2.t.(1/2)+(1/4)+1−(1/4))))−(1/2)∫((d(t^2 +t+1))/(√(t^2 +t+1)))dt  =(1/2)∫(dt/(√((t+(1/2))^2 +((((√3) )/2))^2 )))−(1/2)∫((d(t^2 +t+1))/(√(t^2 +t+1)))  =(1/2)ln{(t+(1/2))+(√(t^2 +t+1)) }−(1/2)×((√(t^2 +t+1))/(1/2))  =(1/2)ln{(t+(1/2))+(√(t^2 +t+1)) }−(√(t^2 +t+1))   =(1/2)ln{((1/x)+(1/2))+(√((1/x^2 )+(1/x)+1))  }−(√((1/x^2 )+(1/x)+1))   I_2 =∫(dx/x^2 )=(x^(−1) /(−1))=((−1)/x)  I_3 =∫((√(1+x+x^2 ))/x^2 )  =∫((1+x+x^2 )/(x^2 (√(1+x+x^2 ))))dx  =∫(dx/(x^2 (√(1+x+x^2  ))))+∫(dx/(x(√(1+x+x^2 )) ))+∫(dx/(√(1+x+x^2 )))  =same as I_1 +∫(dx/(x(√(1+x+x^2 ))))+∫(dx/(√((x+(1/2))^2 +(((√3)/2))^2 )))  =same as I_1 +ln{(x+(1/2))+(√(x^2 +x+1)) }+∫(dx/(x(√(1+x+x^2 ))))  =(1/2)ln{((1/x)+(1/2))+(√((1/x^2 )+(1/x)+1))  }−(√((1/x^2 )+(1/x)+1)) +  ln{(x+(1/2)+(√(x^2 +x+1)) }+∫(dx/(x(√(1+x+x^2 ))))  ∫(dx/(x(√(1+x+x^2  ))))  x=(1/t)  dx=((−1)/t^2 )dt  ∫((−dt)/(t^2 ×(1/t)×(√(1+(1/t)+(1/t^2 )))))  ∫((−dt)/(√(t^2 +t+1)))  =−ln{t+(1/2))+(√(t^2 +t+1)) }  =−ln[((1/x)+(1/2))+{(√((1/x^2 )+(1/x)+1))}]  NOW PLS put the value of I_1 −2I_2 +I_3

121+x+x2+1+x+x2x21+x+x2dxdxx21+x+x22dxx2+1+x+x2x2dxI=I12I2+I3I1=dxx21+x+x2t=1xdxdt=dxx2dt1+1t+1t2tdtt2+t+1122t+11t2+t+1dt=12dtt2+t+112d(t2+t+1)t2+t+1=12dtt2+2.t.12+14+11412d(t2+t+1)t2+t+1dt=12dt(t+12)2+(32)212d(t2+t+1)t2+t+1=12ln{(t+12)+t2+t+1}12×t2+t+112=12ln{(t+12)+t2+t+1}t2+t+1=12ln{(1x+12)+1x2+1x+1}1x2+1x+1I2=dxx2=x11=1xI3=1+x+x2x2=1+x+x2x21+x+x2dx=dxx21+x+x2+dxx1+x+x2+dx1+x+x2=sameasI1+dxx1+x+x2+dx(x+12)2+(32)2=sameasI1+ln{(x+12)+x2+x+1}+dxx1+x+x2=12ln{(1x+12)+1x2+1x+1}1x2+1x+1+ln{(x+12+x2+x+1}+dxx1+x+x2dxx1+x+x2x=1tdx=1t2dtdtt2×1t×1+1t+1t2dtt2+t+1=ln{t+12)+t2+t+1}=ln[(1x+12)+{1x2+1x+1}]NOWPLSputthevalueofI12I2+I3

Terms of Service

Privacy Policy

Contact: info@tinkutara.com